STUDI ANALISIS MOLEKULER DAN KARAKTERISTIK PERTUMBUHAN VIRUS DENGUE DARI PENDERITA DI PROPINSI ACEH TAHUN 2016 - WARDAH, NIM011414153021 (2017)
Dengue disease is still a major health problem in Indonesia, and occurs in all provinces including Aceh. Incidence of the disease in Aceh had increased since 2011 till 2014. However, only limited data about the disease and its causative agent was available. The disease is caused by dengue virus (DENV) which consists of four serotypes (DENV-1, 2, 3, 4). We conducted surveillance in three regions in Aceh province during January-March 2016, namely: Banda Aceh, Lhokseumawe and North Aceh. A total 114 samples of dengue-suspected patients were tested serologically (IgM and IgG, and NS1), and also inoculated in cell C6/36 for observation of CPE, then in vero B1 for immunostaining assays. RT-PCR was performed from samples with NS1 and or CPE and immunostaining-positive. DENV genotyping was performed by sequencing and phylogenetic analysis of envelope (E) gene. To determine the growth characteristics of Aceh’s DENV, replication kinetics of all three serotypes were measured by focus assay methods. Comparation test for DENV replication rates with Kruskal-Wallis (α= 0.05) Results: Based on serological data, 18 patients were primary infection and 60 were secondary infection. A total 24 samples were positive PCR which DENV-2 was predominant (76,2%), followed by DENV-3 (28,5%) and DENV-1 (9,5%). Genotyping revealed circulation of DENV-1 genotype I and DENV-2 genotype cosmopolitan. In Kruskal-Wallis test p=0.000. Conclusion: Three serotypes (DENV-1 genotype I and DENV-2 genotype cosmopolitan and DENV-3) were found to be co-circulating in Aceh between January and March 2016. Comparative analysis showed statistically difference rate of DENV replications (p=0.000).